New species of Ficus sect. Pharmacosycea (Moraceae) from the Andes and Coastal regions of Ecuador - Pederneiras, Leandro Cardoso; Plata-Castro, Ángelo D.; Mitidieri-Rivera, Nicole (Phytotaxa, 2026)
Two new species of Ficus sect. Pharmacosycea subsect. Bergianae from Ecuador are described herein. The first, Ficus montalvoana, occurs at Andean elevations and, among other diagnostic characters such as velutinous leaves, exhibits a peduncle and receptacle significantly smaller than those of its related congener, Ficus dulciaria. The second species, Ficus penafieliae, occurs in western Ecuador and is distinguished by its glabrous leaves and geminate, sessile syconia, which are relatively small compared to those of its related congener, F. crassivenosa. Both species honor two renowned Ecuadorian researchers.